Digital realities: role stress, social media burnout, and e-cigarette behavior in post-90 s urban white-collar workers - Lin, Shihua; Zhang, Jinqi; Wang, Lin; Wang, Shuchuan (Springer Science and Business Media LLC, 2024)
In an era characterized by rapid technological advancements, the paradigm of social media, particularly instant messaging platforms, has witnessed profound evolution. This transformation has redefined how individuals communicate and share information, creating both positive and negative repercussions. A notable surge in social media burnout has emerged among the latter, reflecting shifts in users’ experiences. Concurrently, the digital landscape has become a cornerstone for various aspects of professional, educational, and social endeavors. This transition has given rise to a unique form of stress known as role stress, stemming from the demands of managing multiple roles in the digital sphere. This study focuses on WeChat “Moments” to delve into the intricacies of role stress dynamics among post-90 s urban white-collar professionals. Also, this research addresses the compelling issue of e-cigarette usage, a concern with enduring public health implications. By investigating the interplay of social stress and social adaptation within social media, this study unravels their significant influence on attitudes toward e-cigarette usage among this demographic. The comprehensive examination of role stress, social media burnout, and withdrawal behavior contributes to a deeper understanding of how these constructs intersect in the digital age. This research advances theoretical frameworks and holds practical implications for managing well-being in a digitally driven society, emphasizing the need for policies promoting responsible social media engagement and mental health support.